Exigência nutricional de triptofano para o jundiá (Rhamdia quelen) - Pianesso, Dirleise (2015)
Knowledge about the nutritional requirements of fish is essential to improve the utilization of nutrients the diet. This study estimated the amino acid tryptophan requirement for silver catfish using a biological assay in a completely randomized design with five treatments and four replications. Groups of 30 fish (4.65 ± 0.68 g) were stocked in tanks (125 L) and fed diets mixed, to apparent satiation, containing different concentrations of tryptophan (0.10, 0.18, 0.26, 0.34, 0.42 g-1 tryptophan 100 g diet). After 60 days, were calculated the weight gain, specific growth rate, feed conversion, protein retention coefficient, body composition, somatic indices, and determined the concentrations of plasma metabolites, liver and digestive enzymes. The data were subjected to evaluation by means of nonlinear regression, broken line and polynomial. There was a highly significant effect (P<0.0001) the addition of tryptophan on growth, protein retention coefficient and acid protease activity. Fish fed these concentrations of tryptophan presented no alterations in metabolism and activity of digestive enzymes. The lowest concentration tested (0.10 g tryptophan 100 g-1) showed lower growth and deposition of nutrients in the body. Fish fed inadequate levels of tryptophan have submitted reduced growth, higher hepatosomatic index, alterations metabolics and enzymatic indicating gluconeogenic processes. The estimated amino acid requirement of tryptophan for maximum weight gain and protein retention coefficient is 0.25 to 0.34 g tryptophan 100 g-1 depending on the statistical model used for the estimation.